Structural-functional changes of lymphoid organs under vibration and their correction with the help of essencial phospholipides - S. V. Bobrova; A. V. Efremov; G. M. Vakulin (Бюллетень сибирской медицины, 2002)
The research of lymphoid organs of male rats of Vistar line wich were subjected to vibration with freguency of 32 Hz during 30 days has been conducted. Cytological shifts of the basic structural components of the investigated organs during the vibration period, postcontact rehabilitation period (30, 60 days) and under essencial phospholipides correction were estimated by the methods of light and electron microscopy and morphometry. The analysis of the obtained data demonstrated that the important infringement of lymphoid organs structures takes place. The dynamic study of morphofunctional and ultrastructural changes, cytoarchitectony of parenchymatous stromal compartment gives evidence of the development of degenerate-distrophic processes with mainly involutional character. Pharmacological correction resulted in positive dynamic of cytological shifs and helped to rehabilitation the natural cell phenotype.